Why school communication matters : strategies from pr professionals - Porterfield, Kitty, 1941- (Rowman and Littlefield, 2014)
Why School Communication Matters is an easy-to-use reference for the communication dilemmas that superintendents, principals, and other school leaders face today as they lead faculty and staff, parents and students, neighbors and community leaders. This newly revised edition incorporates the monumental technological changes, including social media that are reframing the way we think and work. The book deals with real life challenges and offers practicable solutions.